An Anesthesia Block Room Is Financially Net Positive for a Hospital Performing Arthroplasty. Issue 15 (1st August 2022) - Toor, Jay; Saleh, Imran; Abbas, Aazad; Abouali, Jihad; Wong, Paul; Chan, Timothy C. Y.; Sarhangian, Vahid
Abstract : Introduction: Regional anesthesia is increasingly used in total joint arthroplasty (TJA). It has shown efficiency benefits as it allows parallel processing of patients in a dedicated block room (BR). However, granular quantification of these benefits to hospital operations is lacking. The goal of this study was to determine the financial effect of establishing a BR using comprehensive operational modeling. Methods: A discrete-event simulation model of daily operating room (OR) patient flow for TJA procedures at a mid-sized hospital was developed. Two scenarios were tested: (1) without and (2) with a BR. Scenarios were compared according to staffing requirements, hours/day, and labor costs. The number of ORs and cases varied from 2 to 6 ORs performing 3 to 5 cases. These results were used as the inputs of a discounted cash flow (CF) model. Discounted CF model outputs were CF, net present value, internal rate of return, and return on investment. Results: Mean time savings of incorporating a BR were 68 min/d (range: 30 to 80 min/d), reducing the OR closing time by 1 hour. Incremental labor costs/day from nurse overtime pay ranged from 2, 025 to 10, 125 with no BR and 1, 595 to 9, 045 with a BR, which resulted in an increase in profit/day from 360 to 1, 605. The CF/annum was 54, 363, the net present value was 213, 082, the internal rate of return was 12%, and the return on investment was 43.61%. Discussion: This study demonstrates that under all scenarios, a BR is more profitable than no BR to a hospital performing TJA via a bundled care or private payer remuneration model. A BR was shown to be financially net positive even when considering the necessary financial investment to establish it. In addition, this study demonstrates the potential of combining discrete-event simulation with financial analyses to assess various operational models of care to improve hospital efficiency, such as dedicated trauma rooms and swing rooms. Level of evidence: Level III